Incorporation Groundwater Recharge with AVSWAT Model Streamflow by Using Water Table Fluctuation - Rahayuningtyas, Christina; Wu, Ray Shyan; Anwar, Ruslin (Fakultas Teknik, Universitas Brawijaya, 2013)
This research investigated contribution of sustainable management water resources in the Upstream Lesti Watershed. The main objective of this research predicted recharge of groundwater using water table fluctuation (WTF). The groundwater recharge prediction will be added as a result from deep aquifer with the performance of AVSWAT (Arc View Soil Water Assesment Tool) model by comparing observed streamflows with simulated streamflows at outlet. The water table fluctuation method from 4 well was used in the Upstream Lesti Watershed to evaluate seasonal and annual variations in water level rise and to estimate the groundwater recharge prediction (deep aquifer). Based on standard values of specific yield and water level rise, the groundwater recharge prediction from the Upstream Lesti Watershed at the outlet of sub basin 39 was 736 mm in 2007; 820,9 mm in 2008; 786,7 mm in 2009; and 306,4 mm in 2010, respectively.Keyword : AVSWAT, Groundwater Recharge, Water Table Fluctuation, Streamflow